Permanent education and vaccination: minimizing missed opportunities (Research, Society and Development, 2020)
Vaccines are essential in the fight against various diseases however, health professionals need to be sensitized to the non-occurrence of missed vaccination opportunities. The aim of this study is to describe the process of Permanent Health Education on Missed Opportunities in a Family Health Unit of Baixada Fluminense. It was conducted an descriptive research on type of action research with 13 workers from the multidisciplinary team. Data in mixed questionnaires, submitted to Content Analysis; and subsequent preparation of intervention plan based on situational strategic planning. The results showed that the team has knowledge about missed opportunities but contributes to their occurrence by: not approaching the population while waiting for care; define previous days for vaccination; false contraindications. It was made An analysis of the causes of the problem in question, defined its critical nodes and created specific operations, culminating in the Intervention Plan. It was concluded this was translated into a Permanent Education strategy that, with the involvement of the entire multidisciplinary team, modified vaccination practices in order to reduce the missed opportunities.